The Grand Jamik Mosque of Pekan Dolok Masihul: The Dynamics of Its Socio-Religious Role, 1872–2025 - Ahmad Rifki Saragih; Muaz Tanjung (Medan Resource Center, 2026)
Mosques have historically functioned as central institutions in the development of Islamic civilization, serving not only as places of worship but also as hubs for social, educational, and religious activities within Muslim communities. This study examines the historical establishment of the Grand Jamik Mosque of Pekan Dolok Masihul and analyzes its socio-religious roles from 1872 to 2025, with a focus on its contribution to local historiography and mosque institutional studies. The research employs a qualitative historical method through stages of heuristics, source criticism, interpretation, and historiography. Data were collected from literature review, archival sources, and interviews with community leaders and mosque administrators. The findings show that the mosque’s establishment is closely linked to the development of the Bedagai region and its role as a center of Islamic growth. The mosque has functioned as a dynamic socio-religious institution that continuously adapts to social changes, particularly in sustaining Islamic education, preserving religious traditions, and strengthening social cohesion. This study highlights the institutional resilience of mosques in rural contexts and argues that their enduring relevance lies in their ability to integrate religious authority with social functions.